Night shift and occupational fatigue among nurses who work 12 hours in Jeddah - Bayan Alanmi; Ruba Alharazi; Hayfa Almutary (Journal of Education and Health Promotion)
The ever-demanding job of nurses necessitates night shift work for 12 hours at various healthcare facilities to improve continuity of care. Working at night is associated with physical and mental stress as it disturbs circadian rhythm, affects sleep, influences dietary and eating routine, and impairs cognitive function. Nursing is a high-demand profession that requires working for longer hours, due to which, nurses are at increased risk of occupational fatigue. This occupational fatigue involves various components of one’s life including poor physical performance, poor mental health, impaired cognition, and sensory overload on account of high work demand but low energy restoration. The current scope review aimed to assess the effect of night shift and occupational fatigue on nurses who work 12 hours. A systemic search of PubMed, EBSCO, CINAHL, MEDLINE, and Google Scholar was conducted. A total of 245 full-text articles underwent eligibility evaluation. In the end, 17 full-text articles were included in this scoping review. This scoping review found that there is a significance positive association of occupational fatigue with 12 hours nightshift work and that chronic fatigue leads to negative emotions, lack of concentration, and decreased motivation and subsequent reduced physical performance. In addition, nurses’ 12 hours nightshift work results in psychological, physical issues including anxiety, depression, burnout, exhaustion, and professional performance as well as affects nurses’ social and quality of life. Therefore, policymakers need to work on circadian rhythm-based interventions considering the work duration, speed of shift change, number of consecutive shifts, and social support.